Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,5.\left(x+35\right)=515\)
\(x+35=103\)
\(x=103-35\)
\(x=68\)
\(b,12.x-33=3^2.3^3\)
\(12x-33=243\)
\(12x=276\)
\(x=23\)
\(d,12.\left(x-1\right):3=4^3-2^3\)
\(12.\left(x-1\right):3=56\)
\(12.\left(x-1\right)=168\)
\(x-1=14\)
\(x=15\)
12x - 33 = 32 . 33
12x - 33 = 35
12x = 35 + 33 = 276
x = 276 : 12
x = 23
12 . x - 33 = 32 . 33
12 . x - 33 = 35
12 . x - 33 = 243
12 . x = 243 + 33
12 . x = 276
x = 276 : 12
x = 23
80-[130-(12-4)^2]=80-[130-8^2]=80-[130-64]=80-66=14
12x-33=3^2.3^3
12x-33=3^5
12x-33=243
12x=243+33
12x=276
x=276 : 12
x=23
541+(218-x)=735
(218-x)=735-541
218-x=194
x=218-194
x=24
a) 70 - 5 ( X-3)=45
5(x-3)=70-45
5(X-3)= 25
x-3=25:5
X-3=5
X=5+3=8
B) 3^x-12=15
3^x=12+15
3^x=27
3^x=3^3
=>x = 3
a) 80 - [130 - (12 -4)2 ]
= 80 - ( 130 - 82 )
= 80 - 116
= -36
b) 541 + (218 - b) = 735
218 - b = 194
b = 24
c) 5(x + 35) =515
x+35 = 103
x = 68
d) 96 - 3(x + 1) = 42
3(x+1) = 54
x+1 = 18
x = 17
12x - 33 = 32 . 33
12x - 33 = 243
12x = 276
x = 23
a
(6x-39):3=201
<<=>6x-39=603
<=>6x=642
<=>107
b
23+3x=5^6:5^3
<=>23+3x=5^3
<=>23+3x=125
<=>3x=102
<=>x=34
c
12.x-33=3^2.3^3
<=>12x-33=243
<=>12x=276
<=>x=23
đây là cách giải của mk:
a, 5(x + 35) = 515
=> x + 35 = 515 : 5
=> x + 35 = 103
=> x = 103 - 35
=> x = 68
b, 12x - 33 = 32 . 33
=> 12x - 33 = 32 + 3
=> 12x - 33 = 35
=> 12x - 33 = 243
=> 12x = 243 + 33
=> 12x = 276
=> x = 276 : 12
=> x = 23
c, 6 . x - 5 = 9
=> 6 . x = 9 + 5
=> 6 . x = 14
=> x = 14 : 6
=> x = \(\frac{2}{3}\)
d, 4(x - 12) + 9 = 17
=> 4(x - 12) = 17 - 9
=> 4(x - 12) = 8
=> 4 . x - 12 = 8
=> 4 . x = 8 + 12
=> 4 . x = 20
=> x = 20 : 4
=> x = 5
a, 5 ( x + 35 ) = 515
x + 35 = 515 : 5
x + 35 = 103
x = 103 - 35
x = 68
b, 12x - 33 = 32 . 33
12x - 33 = 35
12x - 33 = 243
12x = 243 + 33
12x = 276
x = 276 : 12
x = 23
c, 6.x - 5 = 9
6x = 9 + 5
6x = 14
x = 14 : 6
x = \(\frac{7}{3}\)
d, 4.( x - 12 ) + 9 = 17
4 . ( x - 12 ) = 17 - 9
4 . ( x - 12 ) = 8
x - 12 = 8 : 4
x - 12 = 2
x = 2 + 12
x = 14
12x - 33 = 32.3
<=>12x - 33 = 9.3
<=> 12x - 33 = 27
<=> 12x = 27 + 33
<=> 12x = 60
<=> x = 60 : 12
=> x = 5
~~Học tốt~~
\(12x-33=3^2.3\)
\(12x-33=27\)
\(12x=60\)
\(x=5\)
Vậy x = 5